PERBANDINGAN PERTUMBUHAN Aspergillus niger PADA MEDIA POTATO DEXTROSE AGAR (PDA) DAN MEDIA ALTERNATIF DARI SINGKONG, UBI JALAR, DAN BEKATUL - Indah Lestari; Akhmad Mubarok; Imam Agus Faizal (LPPM Universitas Abdurrab, 2024)
Aspergillus niger is one of the fungi that can produce citric acid and is often used in some studies because of its resistance to very low acidic conditions. Potato Dextrose Agar medium is a common medium for culturing fungi in the laboratory. Alternative media are media that use materials from nature whose content is not yet known in detail. Rubber cassava has a carbohydrate content of 98.4674%. The carbohydrate content of white sweet potato is 28.78%. Rice bran has a carbohydrate content of 84.36%. The purpose of this study was to determine the comparison of the growth diameter of Aspergillus niger fungi on Potato Dextrose Agar (PDA) media and alternative media made from cassava, sweet potato, and rice bran. The research used a pure experimental method. Aspergillus niger isolates were observed microscopically, after which they were planted on PDA media and alternative media, incubated at 37Â°C for 72 hours, then the diameter of fungal growth was measured. The results showed that the alternative media that had the largest Aspergillus niger fungal growth diameter compared to PDA media as a control was alternative media from rice bran with the smallest diameter of 40 mm and the largest diameter of 80 mm.